Interleukin-6 is critical in the development of pulmonary vascular disease in Gcn2- deficient mice - Max Schwiening; Qingyue Gao; Mark Southwood; Alexi Crosby; Stephen Moore; Jose A. Valer; Niki Veale; Benjamin J. Dunmore; Paul D. Upton; A. A. Roger Thompson; Nicholas W. Morrell; Stefan J. Marciniak; et al. (Proceedings of the National Academy of Sciences, 2026)
Biallelic mutations in EIF2AK4, encoding Eukaryotic Translation Initiation Factor 2α kinase 4 or General Control Nonderepressible 2 (GCN2), cause pulmonary veno-occlusive disease (PVOD), a fatal form of pulmonary hypertension. The mechanisms linking GCN2 deficiency with pulmonary vascular pathology are poorly understood. To investigate this, we developed two mouse models: genetic ablation of Gcn2 , to mirror GCN2 -mutation positive PVOD, and a pharmacological model using mitomycin C, a drug which can cause PVOD as an idiosyncratic drug reaction. Both models were phenotyped, and lungs from wild-type and Gcn2 -deficient mice were analyzed using single-cell RNA sequencing. We show that homozygous loss of Gcn2 is sufficient to induce mild pulmonary hypertension in mice. Single-cell transcriptomic profiling identified adventitial fibroblasts as the cell population exhibiting the most Gcn2 -dependent transcriptional changes. Pathway analysis revealed upregulation of inflammatory signaling in Gcn2 −/− adventitial fibroblasts. Consistent with this, we demonstrate a proinflammatory phenotype in Gcn2 −/− mouse fibroblasts and in Gcn2 −/− mice. Using a mitomycin C–induced murine model, genetic deletion of interleukin-6 ( Il6 ) rescued the pulmonary vascular phenotype. Furthermore, chronic lipopolysaccharide exposure exaggerated pulmonary hypertension in Gcn2 −/− mice, and Il6 ablation rescued both baseline and lipopolysaccharide-exacerbated disease. Pharmacological inhibition or genetic ablation of the Integrated Stress Response, which can be driven by GCN2-activation, phenocopies Gcn2 deficiency. Therefore, we establish a regulatory effect of an intact GCN2-Integrated Stress Response on IL-6 signaling. Together, we show that interleukin-6 is a critical mediator of both Gcn2 deficiency–associated and mitomycin C–triggered pulmonary vascular disease in mice and highlight IL-6-dependent pathways as potential therapeutic targets.